Minimally Invasive Treatment Options for Hepatic Uveal Melanoma Metastases - Abin Sajan; Samuel Fordyce; Andrew Sideris; Connie Liou; Zeeshan Toor; John Filtes; Venkatesh Krishnasamy; Noor Ahmad; Stephen Reis; Sidney Brejt; Asad Baig; Shaheer Khan; et al. (Diagnostics, 2023)
Uveal melanoma is one of the most common primary intraocular malignancies that accounts for about 85% of all ocular melanomas. The pathophysiology of uveal melanoma is distinct from cutaneous melanoma and has separate tumor profiles. The management of uveal melanoma is largely dependent on the presence of metastases, which confers a poor prognosis with a one-year survival reaching only 15%. Although a better understanding of tumor biology has led to the development of novel pharmacologic agents, there is increasing demand for minimally invasive management of hepatic uveal melanoma metastases. Multiple studies have already summarized the systemic therapeutic options available for metastatic uveal melanoma. This review covers the current research for the most prevalent locoregional treatment options for metastatic uveal melanoma including percutaneous hepatic perfusion, immunoembolization, chemoembolization, thermal ablation, and radioembolization.